Innovation of safety gloves / Mohammad Izwan Hakimie Rohaizad and Muhammad Redza Rosman - Rohaizad, Mohammad Izwan Hakimie; Rosman, Muhammad Redza (2023)
The construction industry in Malaysia has risen to become the fastest growing industry in the world. As the construction industry undergoes rapid transformation, the demand for safety gloves has increased in tandem with industry growth. Safety gloves are one of the crucial Personal Protective Equipment (PPE) for protecting the hands of construction workers on construction sites. Occupational Safety and Health Administration (OSHA) mandates that employers in the construction industry must ensure their employees wear safety gloves when working in environments where there is a risk of hand injury. In the construction industry, safety gloves are important in protecting workers from workplace hazards. Based on the previous studies, there are currently several issues affecting the safety and comfort levels of workers in relation to safety gloves used in construction workspaces. By identifying the main issues, the current study provides an opportunity and platform to propose new innovative ideas to address the challenges. As a result, new solutions are proposed to combat the identified issues.